Effect of Dysphagia on the Older Adults' Nutritional Status and Meal Pattern - Pongsak Saleedaeng; Narumanas Korwanich; Weerasak Muangpaisan; Kanyarat Korwanich (SAGE Publishing, 2023)
Introduction/Objectives: Dysphagia is a widespread clinical condition among older adults. Although known as a risk factor for nutritional status and dehydration, dysphagia also affects meal patterns. This study aimed to determine the relationship between dysphagia and undernutrition, as well as dietary consumption patterns in older adults. Methods: 268 older adults (144 women, 124 men) were included in the study. Mini Nutritional Assessment (MNA), dysphagia assessment (EAT-10), oral examination, and Semi-quantitative Food Frequency Questionnaire (SFFQ) were used for collecting data. Odds ratio and Chi square were used to compare independent variables in subjects with and without undernutrition as well as those who intake texture modified and non-texture modified diet. Results: Mean age of the undernutrition and normal nutrition groups was 68.9 ± 6.1 and 68.8 ± 6.0 years, respectively. The undernutrition group's activities of daily living (ADL) were 19.7 ± 0.9, and the normal nutrition group was 19.8 ± 0.7. Older adults with dysphagia were 4.8 times more likely to experience undernutrition than older adults without dysphagia (95% CI = 1.75-13.13, P  = .002). There was a statistically difference between the meal patterns among the dysphagic older adult group and the normal-swallowing older adults' group at the .05 level. Conclusions: According to this study, dysphagia was associated with the nutritional status of older adults and dietary patterns. The study results suggested some recommendations for dental health personnel on oral care related to dietary consumption and dietary patterns in older adults.